ALK‐positive non–small cell lung cancer: Mechanisms of resistance and emerging treatment options. Issue 16 (22nd May 2014) - Steuer, Conor E.; Ramalingam, Suresh S.
Abstract : Targeted therapy has emerged as an effective treatment option for certain molecular subsets of advanced stage non–small cell lung cancer (NSCLC). The discovery of the echinoderm microtubule‐associated protein like 4–anaplastic lymphoma kinase (EML4‐ALK) translocation as an oncogenic driver has led to the development of novel therapies with activity in vitro and in the clinic. The first‐in‐class tyrosine kinase inhibitor crizotinib is effective against ALK‐positive NSCLC and is currently used as first‐line or salvage therapy in the setting of advanced disease. However, resistance inevitably develops through a variety of mechanisms, including point mutations affecting the fusion protein, activation of bypass signaling pathways, copy number gain of ALK, and other means. Increased understanding of these pathways is essential for tailoring treatment choices to improve outcomes and minimize toxicities. Potent second‐generation ALK inhibitors currently in trials are producing encouraging results in ALK‐positive NSCLC, even in patients with acquired resistance to crizotinib. The success in identifying the ALK translocations and rapidly developing targeted drugs to exploit it paves the way for a better understanding of NSCLC biology and the quest to provide effective, personalized treatment for lung cancer patients. Cancer 2014;120:2392–2402. © 2014 American Cancer Society . Abstract : This review highlights the prevalence and clinical relevance of the EML4‐ALK translocation in non–small cell lung cancer. A major focus has been placed on mechanisms of resistance to crizotinib and the most recent updates on next‐generation therapy.